An??lise quantitativa da percep????o dos stakeholders no processo de gerenciamento de ??reas contaminadas no Brasil - Aguiar, Rizia Miranda (2015)
This dissertation refers to an exploratory study whose major objective was to analyze quantitatively the perception of different stakeholders involved in the management of contaminated areas that may influence sustainable practices in this process. From the literature review was prepared a research instrument in the form of a structured questionnaire with assertions arranged in the form of a Likert scale that was applied to the stakeholders of this process. 141 received questionnaires were tabulated and analyzed by means of multivariate statistical techniques, and the structural equation modeling PLS-PM (Partial Least Squares - Path Model) was used to verify the proposed model. There was a causal relationship between the proposed constructs, pointing to an acceptance of STAKE relationship with PROMOTING and the STAKE and PROMOTING institutional strength define the behavior to adopt SOC_ECO sustainability practices in remediation process, and the ENV construct not It is defined by the behavior of stakeholders, however the hypothesis that the institutional strength impeding defines the behavior to adopt sustainability practices in remediation process is rejected. They identified that the cost issues (impeding) and reaching new customers (PROMOTING), were the assertions that had greater importance in the effectiveness of the adoption of sustainable practices in the management of contaminated areas, indicating a Brazilian concern still facing the associated economic issues these practices.